Perbandingan Dinamika Kelembagaan Ekonomi Islam Brunei dengan India dan Implikasinya Bagi Indonesia: A Comparative Analysis of Islamic Economic Institutional Dynamics in Brunei and India, and Its Implications for Indonesia - Indra Maolana; Naufal Luthfi Alifa (Jurnal Keuangan dan Perbankan Syariah, 2026)
Purpose: This study aims to analyze and compare the dynamics of Islamic economic institutions in Brunei Darussalam and India, as well as to examine their implications for strengthening Islamic economic institutions in Indonesia. Design/methodology/approach: The study employs a comparative qualitative approach using literature analysis from international journals, regulatory documents, and actual institutional practices in both countries. Research Findings: The findings reveal that Brunei, as a Muslim-majority country, has developed Islamic economic institutions in a structured manner through strong state support, integration of maqasid sharia into public policy, and synergy between regulators and Islamic financial institutions. In contrast, India, as a non-Muslim-majority country, demonstrates a more community-based institutional dynamic that emphasizes social inclusion through Islamic microfinance institutions and informal cooperatives. The study suggests that Indonesia can adopt a hybrid institutional model that combines Brunei’s regulatory strength with India’s community participation to build a more adaptive and sustainable Islamic economic ecosystem.  Contribution/Originality/Novelty: The novelty of this study lies in its cross-country comparative analysis that connects institutional characteristics with demographic and political contexts. It offers an alternative institutional model for Indonesia that aligns with the maqasid sharia principles and responds to local socio-economic challenges.